Noneverbal Communication In Content Creator Fiersa Besari’s “Mount Agung, Atap Negeri Bali Part 3” - Rizki Dwi Nur Fajrian; Khaerudin Imawan; Novicky Alban Adiputra (Indonesian Journal Publisher, 2026)
The development of visual-based digital media has made nonverbal communication an important element in conveying messages, especially in video content on the YouTube platform. One content that displays the dominance of nonverbal communication is